Relationships Among Crisis Leadership, Innovation Capability, Implementation of Business Continuity Management, and Sustainable Performance in The Covid-19 Pandemic - Kurniawan, Daniel; Tambunan, Damelina; Dewi, Grace Citra (The South East Asian Journal of Management, 2024)
Research Aims: This study explores the dynamics between crisis leadership (CLE) and sustainable performance (SP) during the COVID-19 pandemic, investigating the mediating roles of innovation capability (IC) and business continuity management (BCM). Design/Methodology/Approach: Utilising questionnaires from 209 respondents and employing quantitative approaches, this research examines the connections between CLE, IC, BCM, and SP, employing PLS-SEM for analysis. Research Findings: CLE significantly influences both IC and BCM, while IC positively impacts SP. This study also highlights the moderating roles of IC and BCM in enhancing organisational resilience. Theoretical Contribution/Originality: The study unveils the substantial influence of CLE on IC and BCM, emphasising their importance in bolstering SP. These findings deepen our understanding of crisis leadership, innovation capability, BCM, and sustainable performance dynamics. Managerial Implication in the Southeast Asian Context: IPMA findings underscore BCM's significance for organisational sustainability, emphasising its alignment with effective CLE. Prioritising BCM alongside fostering IC is essential for organisational adaptability and innovation. Research Limitation & Implications: While focusing on specific variables, the study acknowledges the potential influence of other factors that are not mentioned. Future research should explore these aspects, incorporating the Resource-Based View and Dynamic Capabilities Theory for a comprehensive understanding.